2017
DOI: 10.1016/j.materresbull.2017.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Optical and gas-sensing properties, and electronic structure of the mixed-phase CaCu 3 Ti 4 O 12 /CaTiO 3 composites

Abstract: Optical and gas-sensing properties, and electronic structure of the mixed-phase CaCu3Ti4O12/CaTiO3 composites, Materials Research Bulletinhttp://dx. Graphical abstract A) B)Highlights  CCTO/CTO composites were synthesized by a solid-state reaction using various milling durations; These composites have a broad PL emission band located at 450 nm; CCTO/CTO material was deposited onto an alumina substrate using a screen-printing technique, and hence, could be structured for gas-sensing applications;  Our theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…It is wellknown that during the excitation process of such nanostructured films, the trapping of the electron-hole pairs occurs in the structural defects. In other words, the process is characterized by the involvement of numerous states within the band gap of the system as a result of the relaxation, and an intense emission of the photon also occurs [26,[33][34][35][36][37][38]. Our results revealed that the PL emission behavior of these novel high-quality functional materials is, in turn, actively controlled by their interface features.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…It is wellknown that during the excitation process of such nanostructured films, the trapping of the electron-hole pairs occurs in the structural defects. In other words, the process is characterized by the involvement of numerous states within the band gap of the system as a result of the relaxation, and an intense emission of the photon also occurs [26,[33][34][35][36][37][38]. Our results revealed that the PL emission behavior of these novel high-quality functional materials is, in turn, actively controlled by their interface features.…”
Section: Resultsmentioning
confidence: 86%
“…As a consequence, these findings are commonly consistent with our XRD results for MTO/Si films. Generally, this can attributed to the chemical nature of the reactive species involved, and itis also strongly dependent on the experimental conditions used during the growth of such films [34][35][36][37]. Therefore, these results suggest that the structural changes promoted particularly at the LNO/Si interface, in principle, reduce the polarization, which is capable of populating stable excited electronic states [38,39].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations